The imperatives of the development of the metallurgical complex of Kazakhstan - Zhaleleva, S.Z.; Pasternak , А.А. (BUKETOV BUSINESS REVIEW, 2019)
In the article the issues of development of the metallurgical complex of Kazakhstan are presented, as well as its current state is estimated. The focus of this development is on increasing of the competitiveness of both individual metallurgical enterprises and the country's complex as a whole. For the assessment of the competitiveness of the domestic metallurgical complex, it seems appropriate to consider issues of the economic, social and environmental component of metallurgical companies. In addition, statistical indicators of the metallurgical complex are analyzed, such as gross added value, the share of industries, the volumes of the mining and processing industries, industrial production indices in the country's metallurgical complex, as well as the share of the metallurgical industry in the total industrial output of the Republic of Kazakhstan. For comparison, the experience in regulating industrial sectors in other countries, in particular the metallurgical industry of the Russian Federation, is given, some aspects of which can be used in the preparation of strategic planning documents for the national economy. The article also highlights the main trends in the development of the domestic metallurgical complex, which served to develop the imperatives of its further functioning, in this regard, it is proposed to use the tools of strategic management to increase the level of competitiveness of the metallurgical complex of Kazakhstan.